Universities and Regional Development in Central and Eastern Europe – Far from being obvious - Veréb Miskolczi, Zsófia; Erdős, Katalin (Marketing & Menedzsment, 2020)
THE AIMS OF THE PAPER The increased interest of researchers and policy makers towards higher educational institutions as innovation actors is partly due to internationally well-known examples of the Silicon Valley, Route 128, the Research Triangle or Oxbridge area, just to mention a few. However, the replication of these success stories in other regions that have historically different development paths, institutional, economic and social contexts is not an easy task. The study aims to introduce the most important findings on the role of universities in regional development in peripheral Central and Eastern European countries. A special emphasis is given to those factors that can impede universities’ successful regional developmental role. METHODOLOGY The paper is based on literature survey. MOST IMPORTANT RESULTS The existing empirical evidences suggest that the Central and Eastern European countries face many challenges if they wish to see their universities contributing to the development of their surroundings. The socialist heritage, the low absorptive capacity of companies, the mismatch between the research interest of universities and industry, and the individual motivations all has to be analysed and understood before developing policies and measures. RECOMMENDATIONS The unique historical development path of science, economy and society in Central and Eastern Europe has to be considered at the design and implementation of innovation policies. Failing to do so and simply trying to transfer elements and solutions of high-tech regions is unlikely to lead to success. Acknowledgements: This publication/research has been supported by the European Union and Hungary and co-financed by the European Social Fund through the project EFOP-3.6.2-16-2017-00017, titled "Sustainable, intelligent and inclusive regional and city models".